(untitled) (Journal of Economic Research & Business Administration, 2017)
At the present stage, education as a factor in the formation of human capital has become an element of the strategy of economic growth, has become part of the practice of state regulation of all developed countries of the world. Being an active participant of the Fourth Industrial Revolution, being on the road to modernization to economic growth, integrates into the international competitive system, is an active participant in the implementation of international programs for sustainable development, and pays much attention to the development of education. In this connection, the topic proposed for consideration in this article is very relevant and meets the task facing Kazakhstan – to make education the centerpiece of a new model of economic growth. The aim of the study is to actualize the world experience of education as a factor in the formation of the Cheka in the context of its national development. The scientific and practical significance of the work consists in concretizing ways to improve the quality of education in the process of the Third Modernization of Kazakhstan’s economy. The methodological basis of the study was the work of political economics classics and modern researchers of education in the context of human capital development. The value of the work is that opportunities have been expanded and directions for improving education have been indicated in the formulation of the state policy of Kazakhstan. This research can be useful for industry and state theorists and practitioners, in planning, analyzing and evaluating the state of education and improving human capital.